2014
DOI: 10.1177/0363546514534182
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Risk of Suffering a First-Time Noncontact ACL Injury and Geometry of the Femoral Notch and ACL

Abstract: Morphometric features of both the ACL and femoral notch combine to influence the risk of suffering a noncontact ACL injury. When included together in a multivariate model that adjusts for body weight, the effects of the morphometric measurements are similar in male and female patients. If body weight is not taken into consideration, ACL volume is not associated with a risk in female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
192
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(204 citation statements)
references
References 38 publications
10
192
1
1
Order By: Relevance
“…For example, morphologic features of the femoral notch and the tibial slope have been identified as risk factors for anterior cruciate ligament rupture in the knee. 2,3,19,33 In the shoulder, previous research has shown that GHJ morphology can vary significantly between individuals. For example, an anatomic study by McPherson et al 20 suggested that 95% of 93 cadaveric shoulder specimens analyzed had a glenoid radius of curvature (ROC) ranging from 17 mm to 47 mm.…”
mentioning
confidence: 99%
“…For example, morphologic features of the femoral notch and the tibial slope have been identified as risk factors for anterior cruciate ligament rupture in the knee. 2,3,19,33 In the shoulder, previous research has shown that GHJ morphology can vary significantly between individuals. For example, an anatomic study by McPherson et al 20 suggested that 95% of 93 cadaveric shoulder specimens analyzed had a glenoid radius of curvature (ROC) ranging from 17 mm to 47 mm.…”
mentioning
confidence: 99%
“…The second phase focused on a multivariate evaluation of knee-joint geometry and its effect on the risk of ACL injury. [16][17][18][19][20][21] Detailed results from the first phase are currently under review for publication and, consequently, we can provide only an overview of the study design, but we encourage the reader to consider the detailed findings once they have been published. The findings from the multivariate work in the second phase have been published.…”
Section: Development Of Acl Injury Risk Modelsmentioning
confidence: 99%
“…The findings from the multivariate work in the second phase have been published. [16][17][18][19][20][21] Athletes from 36 institutions (8 colleges, 28 high schools) were monitored prospectively over 4 years for the occurrence of ACL injuries. A total of 109 case participants (70 females, 39 males) who sustained a first-time grade III noncontact ACL injury during involvement in a schoolorganized sport were enrolled in the study.…”
Section: Development Of Acl Injury Risk Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The authors of a study in this month's AJSM attempt to rein in some of this confusion by investigating many of these parameters simultaneously. 34 Although ACL tears would seem to be common occurrences, they are rare enough that prospectively performing MRI examinations of healthy athletes and then waiting for some of them to tear their ACLs would require a very large and expensive study to achieve adequate statistical power. For this reason, prior studies have generally adopted a case-control model, in which the images from athletes with ACL tears have been compared with those who underwent imaging for other reasons.…”
mentioning
confidence: 99%